Hubungan perilaku makan wanita dewasa dengan indeks massa tubuh di rw 003 rt 003 kelurahan bahagia kecamatan babelan – bekasi utara Tahun 2020 - Nina Sri; Laras Pretty Sholeha (Journal Prima Health Science, 2020)
Body mass indeks is a number that connect body weight and height. BMI is a reliable and accurate indicator for measuring body fat. The purpose of this study was to determine the relationship of adult women’s eating behavior with body mass index in RW. 003 RT. 003 Nort Bekasi year 2020. The method used in this research is analytic method with crossectional data collection using a questionnaire as a research instrument and analyzed by bivariate using SPSS 2.0 with chi-square test. The independent variable of this study is adult female eating behavior. The dependent variable of this study is BMI. The sampling technique in this study was by purposive sampling totaling 50 respondents. The result showed there was a relationship between adult female eating behavior with BMI with a p value 0,000 less than 0,05. It is expected that adult women can adopt healty eating behaviors to prevent healt problems, one of which is obesity